DEVELOPMENT OF METHODS OF SIMULATION OF THE INTERACTION OF BIOLOGICALLY ACTIVE SUBSTANCES WITH THE ACTIVE CENTER OF ANGIOTENSIN-CONVERTING ENZYME - A. A. Glushko; A. S. Chiriapkin; V. S. Chiriapkin; A. M. Murtuzalieva; Yu. A. Polkovnikova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2017)
Nowadays cardiovascular diseases are the main cause of death among the population around the word. The development of new drugs, giving a possibility to normalize blood pressure, is a promising direction in the field of pharmacy and medicine. Now inhibitors of angiotensinconverting enzyme (ACE) are widely adopted for the treatment of hypertension and chronic heart failure. The principle of action of ACE inhibitors is based on blocking the conversion of angiotensin I into angiotensin II, which mediates vasodilation.The aim of the work is a selection of methods of lisinopril interaction with the active center of angiotensin-converting enzyme by molecular dynamics methods.Materials and methods. Lisinopril molecule was used as a ligand; the charges of that ligand were calculated with the density functional theory (DFT) and ub3lyp method with the basis sets 6-31G* and 6-311G**. Simulation of 75 ns of molecular dynamics of lisinopril interaction with the active center of ACE was carried out in the Bioevrica program. As a result of molecular dynamics simulation, the trajectory of the "lisinopril-ACE" system was obtained. After that a comparison of ligand conformations at different points in simulation time with the experimental conformation of the value of standard deviation of coordinates of atoms was made.Results and discussion.The results of simulation have showed that lisinopril with the charges corresponding to basis set 6-311G** behaves consistent with the x-ray data in the active center of the ACE, in contrast to lisinopril with the charges calculated by basis set 6-31G*.Conclusion. The methods of lisinopril interaction modeling with the active center of angiotensin-converting enzyme has been selected. The obtained technique can be used for studying the interaction of substances, similar in structure to lisinopril with the active center of the enzyme (ACE).